OPTIMALISASI PENERAPAN STANDAR PELAYANAN PUBLIK DI DINAS TENAGA KERJA KOPERASI DAN UMKM KOTA GORONTALO - Harun, Liana Aulia; Tohop, Rustam; Tantu, Romy (Administratie: Jurnal Administrasi Publik, 2024)
The objective of this study is to examine the Gorontalo City Manpower, Cooperatives, and MSME Agency's optimal implementation of public service standards in terms of service procedures, completion times, costs, service products, facilities and infrastructures, and service providers' competency. This research methodology combines qualitative data analysis with a descriptive technique. Three methods are used to acquire data: documentation, interviews, and observation. The Gorontalo City Manpower, Cooperatives, and MSME Agency has adopted the Optimal Implementation of Public Service Standards in accordance with government regulations and specified provisions, based on the results of research done inside the agency. This condition is evident in the following ways: (1) business actors can easily understand the service procedures; (2) the completion time is limited to one day; (3) there are no service costs because all services are provided without charge; (4) the service product successfully meets the expectations of the business actors; (5) facilities and infrastructures are still incompatible with providing business actors with comforts; and (6) the service officers are competent and have served business actors fairly and pleasantly. Thus, it can be said that there are still issues that need to be fixed with the Gorontalo City Manpower, Cooperatives, and MSME Agency's Optimal Implementation of Public Service Standards.